The Implementation of Work-Based Learning for the Development of Employability Skills of Vocational Secondary School Students Through Teamwork Activity - Subekti, S. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
This study aims to investigate the contribution of teamwork activity through work-based learning to the development of employability skills of SMK (Vocational Secondary School) students. A survey method was employed in this study. The subject of this research are SMK students majoring in farm produce processing agribusiness with bakery competency in Garut. The findings of the study revealed that teamwork activity gives a positive contribution to employability skills of SMK students through the implementation of work-based learning. The contribution of work-based learning to employability skills in the aspect of teamwork is quite significant at the value of 63.5%. The study lead to the conclusion that the implementation of teamwork activity through work-based learning can develop employability skills of SMK graduates.